MANAJEMEN KESAN MELALUI FOTO SELFIE DALAM FACEBOOK: STUDI FENOMENOLOGI PADA MAHASISWA ILMU KOMUNIKASI UMS - Mala, Puspa Aqirul (Universitas Muhammadiyah Surakarta, 2016)
This research explores about selfies phenomenon, especially how people managing their?self-presentation through selfies on the Facebook. Computer Mediated Communications?(CMC) and Erving Goffman?s Dramaturgi become basic theory in this research. Six informants?were active uploaded their selfies and all of them are students of Communications Science?in Muhammadiyah University of Surakarta. Phenomenology qualitative data result that?informants are active managing their visual impression management on Facebook. They?consider that Facebook is a stage and themself is an actor, so they can managing their selfies?easily. Formed the charactheristic of CMC consist of: interactive, editable, de massified, and ?asynchronity.